General rules of evaluating binary number divisibility on prime numbers - Alaa Ghazi Abdulbaqi; Ghadah A. Al-Sakkal; Yasir Hashim (Universitas Ahmad Dahlan, 2022)
This research paper is to define new rule to find the divisibility of stream of binary on any prime numbers 3, 5, 7 …… with reminder 0. In general, the divisibility of binary numbers is most important in many digital circuits and mathematical applications. This paper explains this new rule for evaluating the divisibility of any binary number on any prime number greater than 2. This rule will depend on separating the binary number into blocks of bits then processes each block separately in a special procedure to find the possible divisibility on the prime number. After testing this new rule with prime numbers 3, 5, and 7 as a sample of prime numbers, the finding shows that this rule provides fast and true results.